2004
DOI: 10.1248/cpb.52.976
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manufacturing Parameters on Development of Contraceptive Steroid Loaded Injectable Microspheres

Abstract: The main objective of this work was to develop a system consisting of polymeric microspheres loaded with steroid drugs. The drugs were encapsulated using biodegradable poly(lactide-co-glycolide) (PLG) and poly(e ecaprolactone) (PCL) by double emulsion solvent evaporation method. The lipophilic drugs, levonorgestrel and ethinylestradiol were made soluble by adding ethanol/water mixture. The effects of parameters like polymer concentration and stabilizer concentration were studied on the size, size distribution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Due to its slow degradation [13][14][15], high permeability to many drugs and low toxicity [16], PCL microcarriers consisting of a drug dispersed in spherical polymer matrix have been extensively evaluated for the administration of active compounds over long periods [17][18][19][20]. In these systems, the drug release is governed by factors depending on the polymer (molecular weight, crystallinity), the drug (solubility in water/biological fluids) and their interactions, as well as on the microcarrier's characteristics (drug loading, particle size, porosity) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its slow degradation [13][14][15], high permeability to many drugs and low toxicity [16], PCL microcarriers consisting of a drug dispersed in spherical polymer matrix have been extensively evaluated for the administration of active compounds over long periods [17][18][19][20]. In these systems, the drug release is governed by factors depending on the polymer (molecular weight, crystallinity), the drug (solubility in water/biological fluids) and their interactions, as well as on the microcarrier's characteristics (drug loading, particle size, porosity) [21].…”
Section: Introductionmentioning
confidence: 99%
“…The microspheres were prepared by a w/o/w emulsification–solvent evaporation method as described earlier by us 25, 26. Briefly, a saturated solution of LNG (15 mg) and EE (3 mg) were taken in the ratio of 1:5 in an ethanol:water mixture (7:3) and was emulsified at 4000 rpm for 10 min using a Remi propeller mixer into 10 mL dichloromethane containing 180 mg of polymer.…”
Section: Methodsmentioning
confidence: 99%
“…In our earlier work we have shown that PCL acts as an excellent carrier for contraceptive hormone release 25, 26. The objectives of our work were to entrap both levonorgestrel (LNG) and ethinyl estradiol (EE) within biodegradable microspheres by the w/o/w method and characterize the system with a view of drug content, surface morphology, in vitro degradation, in vitro and in vivo drug release studies.…”
Section: Introductionmentioning
confidence: 99%
“…NET microcrystals were successfully encapsulated into PLA and PLGA microspheres by suspending the NET microcrystals in polymer acetone/chloroform co-solvent solutions followed by adding this suspension into 5 wt% polyvinyl alcohol (PVA) solution to construct the o/w emulsion, and then solvent evaporation. Afterwards, PLGA became the most popular polymer for fabricating microspheres to encapsulate contraceptive APIs including LNG, gestodene and ethinyl estradiol using o/w or w/o/w emulsion/solvent evaporation technique (20)(21)(22)(23)25,27,50,51). Poly(ε-caprolactone) (PCL) is a second popular polymer for fabricating microspheres to encapsulate contraceptive APIs including LNG, ethinylestradiol, norgestrel, progesterone and β-estradiol using o/w or w/o/w emulsion/solvent evaporation technique (49,(52)(53)(54)(55)(56).…”
Section: Microsphere Chemical and Physical Structure And Drug Loadingmentioning
confidence: 99%